2015
DOI: 10.12775/oec.2015.010
|View full text |Cite
|
Sign up to set email alerts
|

Identification of smart specialisations in Polish regions in the context of the EU's new financial perspective 2014-2020

Abstract: The smart specialisation is a new EU’s concept towards the regions. It assumes upgrading of innovation and competitiveness basing  on endogenic potential, in particular, in already existing branches of economy. Smart specialisations should, by definition concentrate economic resources on chosen priorities. Having a smart specialisation will be a pre-condition for access to the UE’s funds in the new financial perspective 2014-2020. Smart specialisation need to be clearly defined and only then can they contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…That helps the Executive to tackle structural regional disparities and promote equality of opportunity for all. It will provide a series of high level strategic objectives, associated policies and indicators with environmental, economic, and societal themes (Kogut-Jaworska, 2015). The overarching aim is to meet wider economic and social needs, while limiting environmental impact and realizing reductions in harmful emissions.…”
Section: The Regional Development Strategymentioning
confidence: 99%
“…That helps the Executive to tackle structural regional disparities and promote equality of opportunity for all. It will provide a series of high level strategic objectives, associated policies and indicators with environmental, economic, and societal themes (Kogut-Jaworska, 2015). The overarching aim is to meet wider economic and social needs, while limiting environmental impact and realizing reductions in harmful emissions.…”
Section: The Regional Development Strategymentioning
confidence: 99%
“…The mezoeconomic perspective of knowledge-based economy has also been developed in literature (Nowakowska et al, 2011;Kondratiuk-Nierodzińska, 2016). Currently, the practical expression of considerations on smart growth at the regional level is the so-called smart specialization (Foray et al, 2009;Kogut-Jaworska, 2015;Miłek & Nowak, 2015). It is based on the synergy of research and innovation with market needs in the identified areas of the greatest potential by focusing resources and avoiding duplication and fragmentation of activities.…”
Section: Introductionmentioning
confidence: 99%